2012
DOI: 10.1080/13691066.2012.688494
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of private equity investment activity: are buyout and venture investors really so different?

Abstract: The information in this working paper does not constitute the provision of investment, legal, or tax advice. Any views expressed reflect the current views of the author(s), which do not necessarily correspond to the opinions of the European Investment Fund or the European Investment Bank Group. Opinions expressed may change without notice. Opinions expressed may differ from views set out in other documents, including other research published by the EIF. The information in this working paper is provided for inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
3
15
1
Order By: Relevance
“…This positive effect is statistically significant at 5 percent level of significance. These findings are supported by a priori expectation, modern portfolio theory, Neo-classical of investment behaviour and the findings of Groh and Liechtenstein (2010), Clarysse et al (2009), Aizenman and Kendall (2008), Kelly (2012), Cherif and Gazdar (2011), Fé lix et al 2013, Oino (2014), Bernoth and Colavecchio (2014) and Oni (2017. This result is inconsistent with the finding of Oino (2014). From our findings, a strong capital market creates a favourable environment for PE exits through initial public offerings and the provision of valuation data for Merger and Acquisition deals.…”
Section: Discussion Of Regression Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This positive effect is statistically significant at 5 percent level of significance. These findings are supported by a priori expectation, modern portfolio theory, Neo-classical of investment behaviour and the findings of Groh and Liechtenstein (2010), Clarysse et al (2009), Aizenman and Kendall (2008), Kelly (2012), Cherif and Gazdar (2011), Fé lix et al 2013, Oino (2014), Bernoth and Colavecchio (2014) and Oni (2017. This result is inconsistent with the finding of Oino (2014). From our findings, a strong capital market creates a favourable environment for PE exits through initial public offerings and the provision of valuation data for Merger and Acquisition deals.…”
Section: Discussion Of Regression Resultssupporting
confidence: 72%
“…The results showed that better business environment and deeper financial markets were important local factors that attract international venture capital. Kelly (2012) investigated the drivers of private equity activity by undertaking a panel data study for 17 European countries. By using the Generalised Method of Moments estimator they found market capitalisation to be an important determinant of PE activity.…”
Section: Theoretical and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous studies (e.g., Kelly, 2012) suggest there are significant differences between VC and BO investments. Therefore, to capture these differences, we use two dummy variables: VC, which is set at 1 when firms have received PE funding as start-up, development or expansion capital and 0 otherwise; and BO, which is set at 1 when PE investors are involved in replacement or buy-out investments and 0 otherwise.…”
Section: Independent Variablesmentioning
confidence: 97%
“…Clarysse, Knockaent and Wright (2009) explained that the amount of early stage venture capital supply is determined by stock market capitalisation. Kelly (2012) identified the positive impact of market capitalisation on venture capital investments and points out that an increase in market capitalisation results in an increase of available funds for venture capital. Furthermore, Cherif and Gazder (2011) found that there is a positive association between market capitalisation and venture capital supply.…”
Section: Literature Reviewmentioning
confidence: 99%